Innate Pathways to B cell Activation and Tolerance - Crampton, Steve P. (2010)
B cells represent an important link between the adaptive and innate immune systems, as they express both antigen-specific B cell receptors (BCRs) as well as various toll-like receptors (TLRs). Several checkpoints in B cell development ensure that self-specific cells are eliminated from the mature B cell repertoire to avoid harmful autoreactive responses. These checkpoints are controlled by BCR-mediated events, but are also influenced by TLR-dependent signals from the innate immune system. Additionally, B cell-intrinsic and extrinsic TLR signaling are critical for inflammatory events required for the clearance of microbial infections. Factors secreted by TLR-activated macrophages or dendritic cells directly influence the fate of protective and autoreactive B cells. Additionally, naïve and memory B cells respond differentially to TLR ligands, as do different B cell subsets. We review here recent literature describing intrinsic and extrinsic effects of TLR stimulation on the fate of B cells, with particular attention to autoimmune diseases.